IDENTIFICATION OF OIL SLUDGE BAGS USING GEOMAGNETIC METHODS IN THE FIELD â€œXâ€ - Irjan, Irjan; Suhartono, Suhartono; Dwi Nur Amalina, Tiara Arum (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2020)
Geophysical research using the geomagnetic method has been carried out in Sekarkurung village, Kebomas district, Gresik district using a Proton Procession Magnetometer (PPM). Geomagnetic data acquisition that has been carried out with an area of 700 x 400 meters has obtained 122 measurement points with a distance between rings of 30 meters. Based on the interpretation of local magnetic field anomaly values that vary from -22 nT to 12 nT. Based on the interpretation of the 2D subsurface modeling, there are 4 types of bodies or layers. The types of layers are: topsoil with a susceptibility value of 0.000020 cgs emu, reef limestone with a susceptibility value of 0.000005 cgs emu, limestone-chalt with a susceptibility value of 0.000026 cgs emu, and limestone with a susceptibility value of 0.000025 cgs emu and oil sludge pouch located at a depth of Â± 50 meters.Â